2014
DOI: 10.1016/j.virusres.2013.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral immunophenotype and viral promoter variants during the asymptomatic phase of feline immunodeficiency virus infection

Abstract: Feline immunodeficiency virus (FIV)-infected cats enter a clinically asymptomatic phase during chronic infection. Despite the lack of overt clinical disease, the asymptomatic phase is characterized by persistent immunologic impairment. In the peripheral blood obtained from cats experimentally infected with FIV-C for approximately 5 years, we identified a persistent inversion of the CD4/CD8 ratio. We cloned and sequenced the FIV-C long terminal repeat containing the viral promoter from cells infected with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
(51 reference statements)
2
19
0
Order By: Relevance
“…This animal has been characterized as a FIV-infected long-term non-progressor (LTNP) cat. [9,11] Additionally, we have demonstrated methylation and deacetylation of histone proteins physically associated with the FIV-promoter in peripheral blood CD4+ T cells isolated during the asymptomatic phase, which is consistent with a condensed chromatin pattern and viral latency. [12] Recently, we demonstrated evidence of active FIV replication in the popliteal lymph nodes in the face of an apparent absence of active viral replication in peripheral blood.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…This animal has been characterized as a FIV-infected long-term non-progressor (LTNP) cat. [9,11] Additionally, we have demonstrated methylation and deacetylation of histone proteins physically associated with the FIV-promoter in peripheral blood CD4+ T cells isolated during the asymptomatic phase, which is consistent with a condensed chromatin pattern and viral latency. [12] Recently, we demonstrated evidence of active FIV replication in the popliteal lymph nodes in the face of an apparent absence of active viral replication in peripheral blood.…”
Section: Introductionsupporting
confidence: 71%
“…Severe peripheral blood CD4+ depletion, as observed for the FIV-infected progressor cats, is a hallmark of FIV infection in cats. [9,11] Due to low animal numbers, statistical comparisons could not be performed. Subjectively, differences in the frequencies of CD8+ and CD21+ leukocytes were not observed in the peripheral blood; however all FIV-infected cats (including the LTNP cat) showed a higher frequency of peripheral CD11b+ cells, which is part of a heterodimeric leukocyte adhesion protein present on feline monocytes, dendritic cells, and neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, relatively few studies have monitored the frequency of CD4+ and CD8+ T cell subsets into the late stages of infection. However, findings from these few studies, including experimental and natural infections, show that CD4+ T cell counts continue to progressively decline to very low levels in blood and lymphoid tissues and may be associated with declining peripheral CD8+ T cell frequencies and clinical signs of immunodeficiencies [7,19,83]. Interestingly, significant declines in CD4+ T cells counts are not always associated with clinical signs of acquired immunodeficiencies and other factors such as environmental stresses may determine disease onset [7,24,79].…”
Section: Cell Reservoirs Of Fivmentioning
confidence: 99%
“…Our group has demonstrated that within this FIV-infected experimental cohort, viral latency in peripheral blood-derived CD4+ T cells is associated with epigenetic modification of histone proteins physically associated with the FIV 5’ LTR (viral promoter) [ 11 , 12 ]. Despite an inactive viral transcription status and a condensed chromatin pattern of the FIV LTR, circulating CD4+ T cell numbers have progressively declined over time in this cohort of cats [ 13 ].…”
Section: Introductionmentioning
confidence: 99%